The US-Japan trade deal: Narrow scope, wider implications - Sonali Chowdhry; Gabriel Felbermayr; Toshihiro Okubo (Kiel Institute for the World Economy (IfW), 2019)
The authors analyze whether the US-Japan Trade Agreement is consistent with GATT Article XXIV that carves out an exception to the WTO's "Most-Favored Nation" (MFN) principle. They conclude that the agreement is unlikely to meet the "substantially all the trade" criterion of GATT Article XXIV since the scope of tariff liberalization is very narrow. The US and Japan have agreed to liberalize just 3.4% and 10% of tariff lines with positive MFN duties, respectively. Key sectors for US exports to Japan such as machinery and instruments are not liberalized under the agreement. Though the market access offered to specific US agri-food products is similar to Japan's commitments under the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), Japan has not "rolled over" the entire CPTPP schedule for the US. Tariff concessions are asymmetric and indicate the relative disadvantage with which Japan entered into bilateral negotiations with the US. Overall, the market access gained by Japan from this deal is highly circumscribed in comparison to the recently implemented EU-Japan Economic Partnership Agreement. – – Die Autoren analysieren, ob das Handelsabkommen zwischen den USA und Japan mit dem GATT-Artikel XXIV vereinbar ist, der eine Ausnahme vom Meistbegünstigungsprinzip (MFN) der WTO vorsieht. Sie kommen zu dem Ergebnis, dass das Abkommen voraussichtlich nicht das Kriterium des "im wesentlichen vollständigen Handels" des Artikels XXIV des GATT erfüllen wird. Die USA und Japan haben sich darauf geeinigt, nur 3,4 % bzw. 10 % der Zollpositionen mit positiven MFN-Zöllen zu liberalisieren. Schlüsselsektoren für US-Exporte nach Japan, wie Maschinen und Instrumente, werden im Rahmen des Abkommens nicht liberalisiert. Obwohl der Marktzugang für bestimmte US-amerikanische Agrarerzeugnisse den Verpflichtungen Japans im Rahmen des "Umfassenden und fortlaufenden Abkommens über die Trans-Pazifische Partnerschaft" (CPTPP) ähnelt, hat Japan den gesamten CPTPP-Plan für die USA nicht übertragen. Die Zollzugeständnisse sind asymmetrisch und offenbaren eine relative schwache Position, von der aus Japan die bilateralen Verhandlungen mit den USA aufgenommen hat. Insgesamt ist der Marktzugang, den Japan aus diesem Abkommen erhält, im Vergleich zum kürzlich umgesetzten Partnerschaftsabkommen EU-Japan stark eingeschränkt.
Keywords: 330; International Trade; US-Japan Relationship; Trade Deal; Tariffs; GATT; Internationaler Handel; Beziehungen USA und Japan; Handelsabkommen; Zölle